Status Gizi Pada Wanita Pranikah di Wilayah Kerja Puskesmas Purwojati - Nur Azizah, Atika; Achyar, Khamidah (INVOLUSI: Jurnal Ilmu Kebidanan, 2022)
A person's level of health is influenced by several factors including nutritional status. The nutritional status of premarital women for three to six months during the preconception period will determine the condition of the baby being born. The proportion of undernourished status in women of childbearing age mostly occurs at the age of 15-19 years as much as 36.3% from the previous year as much as 46.6% then at the age of 20-24 years as much as 23.3%. The purpose of this study was to describe the nutritional status of premarital women in the Purwojati Health Center Work Area. The research method used with descriptive quantitative research is a cohort approach. The research site is in the Purwojati Health Center Work Area. The research sample was all prospective brides who did health checks at the Purwojati Health Center totaling 360 pre-wedding women. The results showed that the most normal nutritional status at the age of 20-35 years was 253 (70.2%) and high school education was 220 (61.2%). While the nutritional status at the age of <20 years was mostly in the category of undernutrition status as much as 15 (4.2%) with a junior high school education level of 20 respondents (5.6%). The conclusion is that the highest proportion of premarital women's nutritional status is in good nutritional status with the age group 20-35 years and high school education level.